Comparative Efficacy Of Herbal-Methionine And Dl-Methionine On Performance Of Commercial Broilers - Bhagora, N.J.; Savaliya, F.P.; Pandya, P.R.; Joshi, R.S.; Patel, A.B.; Hirani, N.D.; Qadri , F.S. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The experiment was conducted on 160 commercial broiler birds from day-old age to 6 weeks of age to study the comparative efficacy of ration containing different concentration of herbal methionine and DL-methionine on their performance in terms of weekly body weight gain, feed consumption, feed conversion ratio, livability and economics. A significant improvement in overall growth and performance was observed in birds supplemented with 50% herbal methionine and 50% DL-methionine as compared to 100% DL-methionine, 100% herbal methionine and 125% herbal methionine. The study also demonstrated that feeding with combination of 50% DL-methionine and 50% herbal methionine is more economical as compared to feeding of 100% DL-methionine, 100% herbal methionine and 125% herbal methionine in commercial broilers.
Keywords: DL-methionine; Herbal methionine; Broilers; Performance